VD_FINDINFO Arrêt / 2025 / 451 vom 4. Juni 2025 - VD Tribunal cantonal (2025)
CURATELLE ÉDUCATIVE, CURATEUR, CHOIXEN GÉNÉRAL, INTÉRÊT DE L'ENFANT | 308 al. 1 CC, 314 CC, 400 al. 1 CC, 400 CC, 423 al. 1 CC